Experimental determination of the contact pressures produced by a nasal continuous positive airway pressure mask: A case study. (August 2022) - Savoldi, Fabio; Svanetti, Lorenzo; Tsoi, James K.H.; Gu, Min; Paganelli, Corrado; Genna, Francesco; Lopomo, Nicola F.
Abstract: Background: A continuous positive airway pressure (CPAP) mask is a respiratory ventilation method used for treating breathing disorders including respiratory failure and obstructive sleep apnoea (OSA). The forces applied by a CPAP mask may affect facial development and lead to pressure ulcers. In an experimental setting, the magnitude and the distribution of the contact pressures developed by a CPAP mask on the face were investigated for providing information aiming at optimizing the design of the device. Materials and methods: A nasal CPAP mask with forehead support was placed via its headgear straps on a rigid phantom head and then a controlled load was incrementally applied via a mechanical testing system (5848 Micro Tester, Instron), up to 4 maximum levels of exerted force, namely 5 N, 10 N, 15 N, and 20 N. Real-time pressure mapping was realized by means of sensor matrixes (I-Scan System, Tekscan) applied on the facial surface in four regions (forehead, nasal bridge, zygoma, and maxilla). The data were then transferred on a virtual model created by 3D scans of both the CPAP mask and the phantom head used in the experiments. Results: At increasing applied force, increases in average contact pressure were present at the zygomatic region (1–8 kPa), nasal bridge (12–14 kPa), and forehead (13–29 kPa), while the maxillary region showed relatively stable values (9 kPa). Despite the overall increase in average contact pressure with increasing applied force, no direct proportionality was present. Contact areas did not show clear increments, despite force may redistribute on a larger area, as sensors did not cover the entire mask perimeter. Peak contact pressure values were somehow affected by pressure concentrations that led to saturation in some areas of the sensors (up to 2% of the sensels). Conclusions: The CPAP mask exerts pressures that may be not uniformly distributed on the face of a subject. This information underlines the clinical importance of assessing both the pressure exerted and the areas that are interested by the mask contact, so as to optimise the CPAP masks design for obtaining a good compromise between ventilation performance and reduction of possible side effects on living tissues.